2013
DOI: 10.1590/s0100-204x2013001200005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters and simultaneous selection for root yield, adaptability and stability of cassava genotypes

Abstract: The objective of this work was to estimate genetic parameters and to evaluate simultaneous selection for root yield and for adaptability and stability of cassava genotypes. The effects of genotypes were assumed as fixed and random, and the mixed model methodology (REML/Blup) was used to estimate genetic parameters and the harmonic mean of the relative performance of genotypic values (HMRPGV), for simultaneous selection purposes. Ten genotypes were analyzed in a complete randomized block design, with four repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
1
12
1
1
Order By: Relevance
“…Possibly, in the present study, the augmented blocks design was not suitable to detect differences for root yield. Farias Neto et al (2013) evaluated ten cassava genotypes in three different locations in the state of Pará, using a randomized complete block design, and identified CVe for root yield of 20.9%, which, in the present work, reached 44.5% for FRY, affecting the detection of genetic variation.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Possibly, in the present study, the augmented blocks design was not suitable to detect differences for root yield. Farias Neto et al (2013) evaluated ten cassava genotypes in three different locations in the state of Pará, using a randomized complete block design, and identified CVe for root yield of 20.9%, which, in the present work, reached 44.5% for FRY, affecting the detection of genetic variation.…”
Section: Resultsmentioning
confidence: 67%
“…A fundamental action in the process of genetic breeding is the genotypic prediction of the most promising genotypes, which depends on the estimation of genetic parameters, as well as on the correlations among traits under selection (Resende et al, 2001;Oliveira et al, 2015). However, researches on estimates of genetic parameters for cassava quantitative traits and of polygenic heritage (Resende, 2002;Ojulong et al, 2008) are still scarce in Brazilian conditions (Barreto & Resende, 2010;Farias Neto et al, 2013). The separation of total variation into inheritable and non-inheritable components is fundamental to define the progress and best strategies for selection.…”
Section: Introductionmentioning
confidence: 99%
“…In the North region, there is little adoption of advanced methods of culture, such as mechanized planting and use of erect cultivars in dense plantations, more commonly used in the Southeast region of Brazil. Moreover, plantations are composed of a mixture of landraces, and generally, farmers from each micro region use their preferred materials, which may be an effect of the high genotype x environment interaction detected for cassava (Farias-Neto et al 2013). This may have contributed for the high genetic variability detected in the germplasm bank.…”
Section: Resultsmentioning
confidence: 99%
“…In studies related to potential rice production, similar proportions were observed between the genotypic variance and the G x E interaction (Colombari Filho et al, 2013), indicating that the effects of the G x E interaction strongly influence the expression of quantitative traits. In contrast, when evaluating the fresh root yield in 10 cassava varieties, Farias Neto et al (2013) reported that most of the variation was due to the environmental effect (79%) over the G x E interaction (18%) and genotypic variation (3%). Furthermore, Oliveira et al (2015) evaluated the effect of drought on genetic parameters and genotypic values for dozens of cassava accessions.…”
Section: Estimates Of Genetic Parametersmentioning
confidence: 98%
“…The AUP-PPD presented a high magnitude (0.72), which would ensure high reliability when selecting the best accessions. In another study related to fresh root yield in cassava, Farias Neto et al (2013) reported success in selecting superior genotypes even when a selective accuracy of moderate magnitude (0.53) was observed. However, those authors noted that an appropriate number of repetitions is essential in field trials for a more efficient and accurate selection, because it can contribute to an increase in the .…”
Section: Estimates Of Genetic Parametersmentioning
confidence: 99%